A Review of Cyber Crime Security : Issues And Challenges - Bhardwaj, Dr Manish (Innovative Research Thoughts, 2017)
The internet's high degree of vulnerability has made online transactions untrustworthy. Cybercrime is growing more serious. In this work, we will define cyber-crime, explain the tools used by criminals to commit their evil deeds, identify the causes of “cyber-crime, how it can be eradicated, examine those involved and their motives, examine how to detect a criminal mail, and finally make recommendations to help curb the rising rate of cyber-crime and criminals.